2012
DOI: 10.1111/j.1360-0443.2011.03740.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a brief intervention for illicit drugs linked to the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) in clients recruited from primary health‐care settings in four countries

Abstract: The Alcohol, Smoking and Substance Involvement Screening Test-linked brief intervention aimed at reducing illicit substance use and related risks is effective, at least in the short term, and the effect generalizes across countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
252
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(269 citation statements)
references
References 20 publications
3
252
1
2
Order By: Relevance
“…Globally, there is now a network of perhaps 10,000 people worldwide who identify addiction science as part of their career identity (Babor, 2012). Membership in the 10 professional societies listed in Table 2.2, which includes both basic and clinical scientists, is comparable to this number.…”
Section: Education and Training Programs In Addiction Studiesmentioning
confidence: 73%
See 2 more Smart Citations
“…Globally, there is now a network of perhaps 10,000 people worldwide who identify addiction science as part of their career identity (Babor, 2012). Membership in the 10 professional societies listed in Table 2.2, which includes both basic and clinical scientists, is comparable to this number.…”
Section: Education and Training Programs In Addiction Studiesmentioning
confidence: 73%
“…Addiction science as such can now be perceived as an independent, professional career (Babor, 2012;.…”
Section: Addiction Science As a Career Optionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reliable and valid brief screening measures to detect alcohol and drug use. [57,58] The World Health Organization (WHO) has developed screenings to identify a continuum of substance use and brief interventions, [59][60][61] and the Committee of the American College of Surgeons has supported routine alcohol screening and brief interventions in Level I Trauma Centers. [62] This support is due to the strong research documentation: the growing field of screening, brief intervention, and referral to treatment (SBIRT) indicates that this method can reduce alcohol use.…”
Section: Substance Use Screening In the Trauma Settingmentioning
confidence: 99%
“…Two recently completed, randomized clinical trials tested the efficacy of SBI and found no significant differences in the reduction of illicit drug use or prescription drug misuse between study groups [11,12]. However, a large multi-center cross-national trial, supported by the World Health Organization (WHO), showed overall effects in primary care settings for reduced drug use in patients receiving SBI, although no significant effects were found for the US sites when examined separately [13]. Further, although SBI for at-risk drug use has not been studied as extensively as at-risk alcohol use [14], earlier clinical studies provide some evidence that SBI may be effective in decreasing at-risk drug use.…”
Section: Introductionmentioning
confidence: 99%